2014
DOI: 10.1007/s10585-014-9685-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotype is associated with survival in breast cancer patients with spinal bone metastases

Abstract: To aid in therapy selection for patients with spinal bone metastases (SBM), predictive models have been developed. These models consider SBM from breast cancer a positive predictive factor, but do not take phenotypes based on estrogen (ER), progesterone (PR) and human epidermal growth factor 2 (HER2) receptors into account. The aim of this study was to ascertain whether receptors are associated with survival, when the disease has progressed up to SBM. All patients who were treated for SBM from breast cancer be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Of the remaining 33 records, nine were removed applying the exclusion criteria. The final set of bibliographic records reviewed was composed of 24 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 33 records, nine were removed applying the exclusion criteria. The final set of bibliographic records reviewed was composed of 24 studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In bone lesions, triple-negative tumors were prevalent. Bollen et al 52 observed that patients with bone metastasis in the triple negative had mean survival of 6.7 months, unlike patients with positive receptors, whose survival was 22.5 months. In our survey, there was no correlation between the presence or absence of metastasis and the basal and non-basal like group.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the classic parameters, like tumor size staging, axillary nodule and metastasis (TNM) and cell proliferation markers, other tumor markers have been used to predict tumor behavior, and the response to therapy in breast cancer. Among the markers verified by the immunohistochemical test, the most used in clinical practice are hormone receptors and HER-2 52 . The normal breast cell presents estrogen and progesterone receptors in their nuclei, detected through the immunohistochemical method.…”
Section: Discussionmentioning
confidence: 99%
“…We found an age of more than 50 years, the presence of multiple SBM and triple negative phenotype to be associated with a worse prognosis after first diagnosis of bone metastases. In a recent study Bollen et al [ 18 ] reported a median survival time of 22.5 months (95 % CI 18.0–26.9) for the receptor positive category and 6.7 months (95 % CI 2.4–10.9) for the triple negative category ( p < 0.001). Therefore, patients with bone metastases from triple negative breast cancer have a significantly worse prognosis than those with a receptor positive phenotype.…”
Section: Discussionmentioning
confidence: 99%